Efficacy of combined rigid and flexible ureteroscopy for complex ureteral stones in type 2 diabetes mellitus - Jiang, Liang; Sun, Shu-Ben; Miao, Qi-Long; Yan, Ze-Jun (Frontiers in Endocrinology, 2025)
BackgroundType 2 Diabetes Mellitus (T2DM) patients with complex ureteral stones face significant challenges in terms of treatment outcomes, including higher risk for complications such as sepsis and prolonged recovery times. The efficacy of combined rigid and flexible ureteroscopy in managing these stones in T2DM patients remains underexplored.MethodsA retrospective cohort study was conducted at our hospital from January 2021 to August 2024. The study included patients aged 18–65 years diagnosed with T2DM and complex ureteral stones (size >1 cm, multiple stones, or those in difficult-to-reach areas). Exclusion criteria involved uncontrolled urinary tract infections, renal malformations, and other significant comorbidities that could hinder surgical success. A total of 182 patients were included, with 93 receiving combined rigid and flexible ureteroscopy (observation group) and 89 undergoing percutaneous nephrolithotomy (PCNL) (control group). The study followed STROBE guidelines, and ethical approval was obtained. Preoperative blood glucose control and surgical interventions were managed in accordance with standard protocols.ResultsThe observation group exhibited superior perioperative outcomes, with significantly shorter surgery time, less intraoperative blood loss, and a reduced duration of hematuria compared to the control group. Stone clearance at 7 days postoperatively was significantly higher in the observation group (54.84%) compared to the control group (39.33%) (P=0.036). Additionally, CRP levels were lower in the observation group at 3 and 5 days postoperatively, indicating less postoperative inflammation. The incidence of postoperative sepsis was significantly associated with female gender, age ≥60, BMI ≥25 kg/m², preoperative positive urine culture, and elevated CRP and fasting plasma glucose (FPG) levels.ConclusionsCombined rigid and flexible ureteroscopy offers a promising approach for managing complex ureteral stones in T2DM patients, providing better early stone clearance, reduced postoperative complications, and improved recovery outcomes compared to percutaneous nephrolithotomy. Risk factors for postoperative sepsis in this patient population include older age, female gender, higher BMI, preoperative urine culture positivity, and elevated CRP and FPG levels. Further studies are necessary to confirm long-term benefits and optimize sepsis prevention strategies.